Post-exposure HIV prophylaxis following sexual exposure: a retrospective audit against recent draft BASHH guidance. Issue 3 (26th May 2006) - Day, S; Mears, A; Bond, K; Kulasegaram, R
Abstract : Objectives: To retrospectively audit the management of post-exposure HIV prophylaxis following sexual exposure (PEPSE) against the British Association for Sexual Health and HIV 2004 draft guidance. Methods: A retrospective review of case notes from January 2000 to November 2004. The draft guidelines were not adopted into clinical practice during the study period. Results: 76 patients received PEPSE. 79% (95% CI 68.08 to 87.46) of PEPSE prescriptions were given for exposures that were in accordance with the guidelines' recommended indications (target 90%). 87% (95% CI 77.13 to 93.51) of PEPSE was prescribed within 72 hours of risk exposure (target 90%). 91% (95% CI 81.94 to 96.22) of recipients received a recommended antiretroviral combination. 53% (95% CI 40.84 to 64.21) of recipients completed the PEPSE course (target 75%). 45% of patients attended for the 3 month follow up HIV test but only 12% (95% CI 5.56 to 21.29) attended for both the 3 month and 6 month HIV test (target 75%). Conclusion: PEPSE is predominantly being prescribed for recommended indications and is dispensed within 72 hours of risk exposure. PEPSE completion rates and attendance for 3 months and 6 months post-exposure HIV testing need improving, perhaps by introducing a PEPSE clinic.